Land tenure insecurity and rural‐urban migration in rural China1. (25th June 2014) - Ma, Xianlei; Heerink, Nico; van Ierland, Ekko; Shi, Xiaoping
Abstract: This paper examines the impact of land tenure security perceptions on rural‐urban migration decisions of rural households, using data collected in Minle County in Northwest China. We find that tenure security perceptions play a significant role in household migration decisions in villages without well‐functioning land rental markets but not in villages where the land rental markets are more developed. In villages with underdeveloped land rental markets, households that expect that no land reallocations will occur within their village in the near future are less involved in migration, while households that attach a greater importance to land certificates in protecting land use rights are more involved in migration.